Social exclusion and including the excluded: a perspective - Sekher, Madhushree; Carciumaru, Radu (Including the excluded in South Asia, 2019)
The development literature in recent years has seen the emergence of the concept of ‘social exclusion’, which focusses attention on the relational aspects of deprivation. Social exclusion may be regarded as intrinsic to deprivation or deprivation in itself. It could also be seen as instrumental in leading to other aspects of relative deprivation reflected in socio-economic disparities. Social exclusion in its multiple dimensions, also, provides a useful framework to capture the processes underlying group-level inequalities and poverty in a society. Seen from this lens, social and political participation is important for social inclusion, because deprivation is not just income poverty. Political engagement and social interaction are two lenses for accessing the inclusion of the socially included.